1x-13=7x-133

Simple and best practice solution for 1x-13=7x-133 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x-13=7x-133 equation:



1x-13=7x-133
We move all terms to the left:
1x-13-(7x-133)=0
We add all the numbers together, and all the variables
x-(7x-133)-13=0
We get rid of parentheses
x-7x+133-13=0
We add all the numbers together, and all the variables
-6x+120=0
We move all terms containing x to the left, all other terms to the right
-6x=-120
x=-120/-6
x=+20

See similar equations:

| 53/10+(-v)=3.8 | | 1/3=n/3 | | x-50=14-3x | | 4(1+4K)=6k+14 | | -5+4(1-3z)=22 | | -8k+8(4-6k)=-23-k | | 5+5(a-2)=2(a+6)+4 | | 32=-7+6(c-5) | | 32=-7+6(c-5 | | 26/x=24/16 | | 9f=f+9 | | 180-6a=4+12 | | 21-4=2t+2+3t | | -1/6x+2.5=1/4x+1.25 | | x2-4x-11=11 | | 3.5+2t=19 | | -6n-4-9=22 | | 3x-45=03 | | 50=e.15 | | 1/3t-4=7 | | 3t-6=21 | | 375=3n | | 3(6d+5)=-33+8d | | 4x/2-5/6=x/3 | | 7/4r=49 | | 5x*4=3x | | 4x-2(-10)=24 | | 13s+-11s−-12s−-3=-11 | | 4x+4-3=4x+8 | | 4(9y-5=10(3y+17)-40 | | 4x=21/2 | | 4-12*b=-27 |

Equations solver categories